Verificação formal de um protocolo de rede sem fio através de model checking - Rosas, Fabiano Almeida (2014)
This work consists of the application of the model checking technique to the formal specification, modeling and formal verification of the basic access method of the IEEE 802.11 standard medium access control protocol distributed coordination function (DCF). The modeling was made assuming nodes with saturated traffic and all stations starting at the same time. The purposed model admits typical configuration parameters of a IEEE 802.11 a/b/g network, such as number of nodes, channel width, data rate and packet size. Using the UPPAAL model checker, properties related to the minimum time needed for all the stations to transmit successfully were formally verified. This work intends to fill a gap that exists with relation to the formal modeling of the IEEE 802.11 DCF and serve as a basis for the formal verification of new 802.11 DCF variations.